Review paperThe possibilities and principles of methotrexate treatment of psoriasis – the updated knowledge - Czarnecka-Operacz, Magdalena; Sadowska-Przytocka, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Psoriasis is a chronic multifactorial disease affecting 2–4% of the general population. Due to its nature, psoriasis has a negative impact on the quality of life of patients. Therefore, the choice of an appropriate and individually tailored treatment controlling the symptoms of the disorder is necessary and continues to be a challenge for dermatologists. Therapeutic modalities in psoriasis should on the one hand be effective and on the other hand present a good safety profile. Methotrexate (MTX) is one of treatment options for psoriasis and can be administered both as monotherapy or in combination schemes. The paper presents the current state of knowledge about the possible treatment of psoriatic patients with MTX according to contemporary guidelines.